μ-opioid receptor availability is associated with sex drive in human males - Nummenmaa Lauri; Jern Patrick; Malen Tuulia; Kantonen Tatu; Pekkarinen Laura; Lukkarinen Lasse; Sun Lihua; Nuutila Pirjo; Putkinen Vesa (SPRINGER, 2022)
The endogenous mu-opioid receptor (MOR) system modulates a multitude of social and reward-related functions, and exogenous opiates also influence sex drive in humans and animals. Sex drive shows substantial variation across humans, and it is possible that individual differences in MOR availability underlie interindividual of variation in human sex drive. We measured healthy male subjects' (n = 52) brain's MOR availability with positron emission tomography (PET) using an agonist radioligand, [C-11]carfentanil, that has high affinity for MORs. Sex drive was measured using self-reports of engaging in sexual behaviour (sex with partner and masturbating). Bayesian hierarchical regression analysis revealed that sex drive was positively associated with MOR availability in cortical and subcortical areas, notably in caudate nucleus, hippocampus, and cingulate cortices. These results were replicated in full-volume GLM analysis. These widespread effects are in line with high spatial autocorrelation in MOR expression in human brain. Complementary voxel-based morphometry analysis (n = 108) of anatomical MR images provided limited evidence for positive association between sex drive and cortical density in the midcingulate cortex. We conclude that endogenous MOR tone is associated with individual differences in sex drive in human males.